HUBUNGAN IMPLEMENTASI TEKNOLOGI INFORMASI (SIMRS) DENGAN EFISIENSI PENANGANAN PASIEN DI IGD RUMAH SAKIT ISLAM SULTAN HADLIRIN JEPARA - Rita Irawati; Ratna Ratna; Akbar Amin Abdullah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
RSI Sultan Hadlirin Jepara is a type C private hospital that has implemented a web-based hospital management information system (SIMRS), including in the Emergency Room unit. This system allows medical personnel to input patient data digitally, monitor the status of treatment rooms, and accelerate communication between service units. Objective: To determine the relationship between the implementation of Information Technology (SIMRS) and the efficiency of patient care in the Emergency Room (IGD) of Sultan Hadlirin Islamic Hospital Jepara. Method: This study uses a quantitative method with a correlational approach. The study population is medical personnel and administrative staff in the Emergency Room of Sultan Hadlirin Islamic Hospital Jepara. The research sample is 30 respondents. The results of the correlation analysis show a positive and significant relationship between the implementation of SIMRS and the efficiency of patient care, with a correlation coefficient value of r = 0.652 and p <0.05. Conclusion: There is a relationship between the implementation of Information Technology and the efficiency of patient care.